2015
DOI: 10.1088/0031-8949/90/4/045701
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic action of CuAlS2microparticles and nanoparticles in cellulose pyrolysis

Abstract: This paper explores the catalytic action of as-synthesized CuAlS 2 microparticles and nanoparticles on cellulose pyrolysis. The CuAlS 2 microparticles were synthesized by heating precursor elements at high temperatures in an evacuated quartz ampoule. CuAlS 2 nanoparticles were synthesized at ambient temperature by using a simple wet chemical technique. Before using the microparticles and nanoparticles for catalytic study, they were comprehensively characterized. The thermal analysis, including catalytic study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several articles have pointed out that for synthesizing CuAlS 2 , the film must be annealed at a temperature >800 °C. [ 140 ] This high synthesis temperature is not suitable for the perovskite device fabrication. Other low temperature‐based techniques must be developed for the application in the field of PSCs.…”
Section: Cu‐based Ternary Sulfidesmentioning
confidence: 99%
“…Several articles have pointed out that for synthesizing CuAlS 2 , the film must be annealed at a temperature >800 °C. [ 140 ] This high synthesis temperature is not suitable for the perovskite device fabrication. Other low temperature‐based techniques must be developed for the application in the field of PSCs.…”
Section: Cu‐based Ternary Sulfidesmentioning
confidence: 99%
“…5 As it is analogous to indium, CuAlS 2 presents a chalcopyrite structure 6 and promising optical properties. 8 Among its reported applications are biological labels, 8 active layer in LEDs, 7 artificial leaves for photocatalytic reduction of CO 2 , 5 in vitro marking of cancer cells for fluorescence microscopy analysis, 8 catalysis of the cellulose pyrolysis, 9 and as a hole transport layer in hybrid solar cells. 4 When used in core/shell structures, Bhattacharyya et al 7 have shown that copper aluminum sulfide quantum dots present high quantum yield (63%) and long PL lifetime (∼1500 ns), showing potential to be applied in LEDs.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 17 Catalytic pyrolysis is impacted by the composition and size of the catalyst, with smaller nanoparticle catalysts performing better than larger, micron-sized structures. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many of these catalysts show diminishing returns, with even highly robust silica/carbon nanocomposite catalysts optimized for reusability, showing approximately 10% loss after two reuses . Catalytic pyrolysis is impacted by the composition and size of the catalyst, with smaller nanoparticle catalysts performing better than larger, micron-sized structures …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation